STUDY OF CHANGES IN TABLA PLAYING IN MADHYA PRADESH: मध्यप्रदेश में तबला वादन में आये परिवर्तनों का अध्ययन - Swarnakar, Rahul (International Journal of Research -GRANTHAALAYAH, 2015)
(1) Sound-oriented tabla Under this, the players play various types of new experiments in relation to the sound of tabla tasir and their imaginations, mainly because of modern day features such as microphones, speakers etc. Their sound is displayed by controlling their playing materials according to their capacity to expand, which is the most important achievement of today's era. (2) Academic Head Tabla Under this, the playing material of the tabla is used according to the prescribed literature and scripture. In this style there is an emphasis of bonds and lack of freedom. This style continues from early education to the next. Over time, this style grows according to knowledge. This type of tabla has been played by our older generations. (1) ध्वनि प्रधान तबला इसके अंतर्गत तबले की तासीर एवं अपनी कल्पना शक्तियों को जीवंत रूप देने के लिए वादक कई तरह के नए प्रयोग ध्वनि के सम्बंध में करते हैं जिसका मुख्य कारण आधुनिक समय की सुविधाएँ जैसे माइक्रोफोन, स्पीकर आदि हैं। इनकी ध्वनि विस्तार क्षमता के अनुरूप ही अपनी वादन सामग्री को नियंत्रित करके प्रदर्शित किया जाता है जो आज के युग की सबसे महत्वपूर्ण उपलब्धि है। (2) अकादमिक प्रधान तबला इसके अंतर्गत तबले की वादन सामग्री निर्धारित साहित्य एवं शास्त्र के अनुसार प्रयोग की जाती है। इस शैली में बंधनों का जोर होता है तथा स्वतंत्रता का अभाव। यह शैली प्रारंभिक शिक्षा से लेकर आगे तक भी जारी रहती है। समय के साथ-साथ यह शैली ज्ञान के अनुसार बढ़ती रहती है। इस तरह का तबला हमारी पुरानी पीढ़ियाँ बजाती आ रही हैं।